Assessing quality of life in German, French, Italian and Polish smart cities: Identifying the need for further development - Brian F. G. FABRÈGUE; Andrea BOGONI (Smart Cities and Regional Development Journal)
The concept of smart cities has gained significant attention in recent years, as urban areas worldwide seek to leverage technology and innovation to enhance their residents' quality of life. It is agreed that one of the core objectives of the smart cities is the optimisation of quality of life and resident satisfaction. This research endeavours to explore the relationship between smart city rankings and quality of life in four European countries: Germany, France, Italy, and Poland. In doing so, we encountered a multitude of complexities and nuances. While the concept of smart cities holds great promise for urban development and enhancing residents' well-being, the current methodologies for comparing smart cities and assessing quality of life require refinement and standardization. Addressing these challenges will not only advance our understanding of the impact of smart city initiatives but also pave the way for more effective urban planning and policy decisions to improve the overall quality of life in urban areas.